A method for preparing back grid line of solar cell

By electrochemical etching in the laser film opening area on the back of the solar cell, the surface roughness is increased and electroplating is carried out, the problem of gate line bonding caused by electroplating on the polishing surface is solved, and the cost is low, process simplified, and binding force is improved. Effect.

CN117810306BActive Publication Date: 2025-02-18TRINA SOLAR ENERGY (DONGTAI) OPTOELECTRONICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311863616.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-02-18
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

In the prior art, when preparing the back gate lines of solar cells, polished surface plating leads to poor gate lines binding forces, and traditional processes increase equipment costs and process complexity.

Method used

Electrochemical etching is performed on the laser film open area on the back of the solar cell to increase the surface roughness, and the power supply and cathode electrode are added to the original hydrofluoric acid tank body to form the back gate line.

Benefits of technology

This method improves the bonding force between the back of the solar cell and the metal gate line, which is low in cost, does not add additional processes and equipment, does not affect the electroplating process time, and does not damage the battery body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117810306B_ABST
    Figure CN117810306B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a back grid line of a solar cell, the method comprising: (1) performing laser film opening on the back of the solar cell in the area to be electroplated with the back grid line; (2) cleaning and removing the oxide layer in the laser film opening area on the back of the solar cell; (3) using the laser film opening area on the back of the solar cell as an anode, electrochemically etching the laser film opening area to increase the roughness of the laser film opening area; (4) electroplating the back grid line in the laser film opening area. The method of the present invention has low cost, does not damage the battery body, does not add additional processes, and does not increase the electroplating process time, and can achieve the improvement of the grid line bonding force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solar cells, and in particular to a method for preparing a back grid line of a solar cell and application thereof. Background Art

[0002] Metallization is one of the key processes in the preparation of photovoltaic cells. The traditional process mainly uses silver paste to make solar cell electrodes. For various high-efficiency battery technologies, the cost of silver paste is the second largest cost after silicon wafers. Especially for TOPCon and HJT technologies, the cost of silver paste has increased significantly from 10-11% of PERC to more than 16%-24%, becoming an important factor restricting its industrialization and promotion.

[0003] Electroplating metallization (Ni / Cu / Ag or Cu / Ag) can meet the requirements of this type of solar cell for low temperature process, low cell material cost and high conductivity double-sided metal grid. For TOPCon solar cells, the combination of double-sided laser contact opening (LCO) and Ni / Cu / Ag plating enables the preparation of high-conductivity grid lines with low contact resistance on the boron emitter on the front surface and TOPCon on the back.

[0004] The back of the TOPCon cell is polished to reduce the loss of back light, but the polished surface has poor grid line bonding due to its small specific surface area during electroplating.

[0005] At present, electroplating of polished surfaces uses chemical nickel plating or nickel evaporation to improve the bonding strength of the grid lines. Some also use secondary lasers to increase the surface roughness to improve the bonding strength of the grid lines. However, chemical nickel plating requires annealing to improve the bonding strength of the coating, which requires an annealing furnace to be added after chemical nickel plating, which increases the cost of electroplating. In addition, electroplating copper after annealing requires acid activation to remove the surface oxide layer. The increase in processes makes it impossible to complete the nickel plating and copper plating solution on one device. Evaporated nickel requires the addition of electron beam evaporation equipment before electroplating, which has high equipment costs. In addition, after nickel plating, the evaporated nickel layer in the non-grid line area needs to be removed, and acid activation needs to be added before electroplating to remove the surface oxide layer, which is a complicated process. Although the secondary laser method has a simple process, it will increase the laser film opening time and the laser itself will damage the film opening area. Performing a secondary laser will increase the damage. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing a back grid line of a solar cell and an application thereof.

[0007] The present invention provides a method for preparing a back grid line of a solar cell, the method comprising the following steps:

[0008] (1) performing laser film opening on the back side of the solar cell in the area where the back side grid lines are to be formed;

[0009] (2) Cleaning and removing the oxide layer in the laser-opened area on the back of the solar cell;

[0010] (3) using the laser-opened film area on the back of the solar cell as an anode, electrochemically etching the laser-opened film area to increase the roughness of the laser-opened film area;

[0011] (4) Make backside grid lines in the laser-opened area.

[0012] According to the method of the present invention, in step (3), the positive electrode of the power supply is connected to the metal grid line of the front structure of the solar cell to form the anode.

[0013] According to the method of the present invention, in step (3), the anodic oxidation current density in the electrochemical etching is 0.5A / dm 2 ~2A / dm 2 , preferably 1A / dm 2 ~1.5A / dm 2 ;

[0014] The temperature of the electrochemical etching is 10°C to 30°C, preferably 18°C ​​to 25°C;

[0015] The electrochemical etching time is 30S to 85S, preferably 40S to 60S.

[0016] According to the method of the present invention, step (2) and / or step (3) are performed in a hydrofluoric acid electrolyte;

[0017] Preferably, a cathode is added to the hydrofluoric acid electrolyte, and the cathode is preferably a titanium cathode;

[0018] More preferably, the surface of the titanium cathode is plated with platinum or rhodium-iridium alloy.

[0019] According to the method of the present invention, the hydrofluoric acid concentration of the hydrofluoric acid electrolyte is 1wt% to 3wt%, preferably 1.4wt% to 1.8wt%; and / or

[0020] NH4F is used to adjust the pH value of the hydrofluoric acid electrolyte to 3-4, preferably 3.4-3.8.

[0021] According to the method of the present invention, in step (2), the temperature for cleaning and removing the oxide layer is 10° C. to 30° C., preferably 18° C. to 25° C.;

[0022] The time for cleaning and removing the oxide layer is 25S to 60S, preferably 30S to 50S.

[0023] According to the method of the present invention, in step (1), the width of the pattern formed in the laser film opening area is 35 μm to 60 μm, preferably 40 μm to 45 μm.

[0024] According to the method of the present invention, the solar cell is a TOPCon cell or a HJT cell.

[0025] According to the method of the present invention, in step (4), the material of the back gate line is selected from one or more of the following: Ag, Cu, Ni, Sn.

[0026] The preparation method of the present invention may have but is not limited to the following beneficial effects:

[0027] The preparation method of the present invention adds a power source and anode and cathode to the hydrofluoric acid tank for electroplating the original oxide layer, and increases the surface roughness in the laser film opening area by electrolytic etching. The method of the present invention has low cost, does not damage the battery body, does not add additional processes, and does not increase the electroplating process time, and can achieve the improvement of the grid line bonding force. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram showing the electrochemical etching of the doped polysilicon layer in the laser-opened film area in Example 1 is shown.

[0029] Figure 2 Shows Figure 1 A local enlarged view corresponding to area a in the middle.

[0030] Figure 3 A schematic diagram showing the battery structure after electrochemical etching in Example 1.

[0031] Figure 4 Shows Figure 3 The local enlarged image corresponding to area b.

[0032] Figure 5 A schematic diagram showing the front grid line structure of the battery in Example 1.

[0033] Figure 6 The transmission electron microscope image of the laser-opened film area in Example 1 before electrochemical etching is shown.

[0034] Figure 7 The transmission electron microscope image of the laser-opened film area of ​​Example 1 after electrochemical etching is shown.

[0035] Description of reference numerals:

[0036] 1. Power supply; 2. Anode; 3. Cathode; 4. Laser film opening area before electrochemical etching; 5. Battery front grid line; 6. Electrolyte; 7. TOPCon battery side; 8. Laser film opening area after electrochemical etching; 9. TOPCon battery front grid line structure; 10. Battery front main grid; 11. Battery front fine grid; 12. PAD point. DETAILED DESCRIPTION

[0037] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.

[0038] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.

[0039] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0040] Before describing the technical solution of the present invention, the terms used in this article are defined as follows:

[0041] The term "TOPCon cell" refers to: Tunnel Oxide Passivated Contact Cell, tunnel oxide passivated contact cell.

[0042] The term "HJT battery" refers to: Hereto-junction with Intrinsic Thin-layer Cell, heterojunction battery.

[0043] The present invention provides a method for preparing a back grid line of a solar cell, the method comprising the following steps:

[0044] (1) performing laser film opening on the back side of the solar cell in the area where the back side grid lines are to be formed;

[0045] (2) Cleaning and removing the oxide layer in the laser-opened area on the back of the solar cell;

[0046] (3) using the laser-opened film area on the back of the solar cell as an anode, electrochemically etching the laser-opened film area to increase the roughness of the laser-opened film area;

[0047] (4) Electroplating is performed in the laser-opened area to form backside gate lines.

[0048] The method of the present invention increases the surface roughness of the laser-opened film area on the back of the battery by electrolytic etching, thereby improving the bonding strength between the back of the battery and the metal grid line. In a specific embodiment, the laser-opened film area on the back of the battery is electrochemically etched by adding a power supply and anodes and cathodes to the original hydrofluoric acid tank for removing the oxide layer. Compared with traditional chemical nickel plating, nickel evaporation and secondary laser methods, this method is low in cost, does not add additional processes and equipment, does not increase the electroplating process time, does not damage the battery body, and can achieve the improvement of the grid line bonding strength using the original equipment.

[0049] According to one embodiment of the present invention, in step (3), the positive electrode of the power supply is connected to the metal grid line of the front structure of the solar cell to form the anode.

[0050] Taking the TOPCon battery as an example, a cathode is added to the electrolyte tank, connected to the negative electrode of the power supply, and connected to the positive electrode of the power supply with the metal grid line on the front of the TOPCon battery. Since the passivation layer on the back of the TOPCon battery is not conductive, the electrolytic anode reaction occurs in the doped polysilicon layer in the laser-opened area on the back of the TOPCon battery. The surface roughness of the doped polysilicon layer in the laser-opened area is increased through electrochemical etching, thereby improving its bonding strength with the metal grid line generated in the subsequent electroplating step.

[0051] According to one embodiment of the present invention, in step (3), the anodic oxidation current density in the electrochemical etching is 0.5 A / dm 2 ~2A / dm 2 , preferably 1A / dm 2 ~1.5A / dm 2 ;

[0052] The temperature of the electrochemical etching is 10°C to 30°C, preferably 18°C ​​to 25°C;

[0053] The electrochemical etching time is 30S to 85S, preferably 40S to 60S.

[0054] By controlling the anodic oxidation current density, etching temperature and etching time of electrochemical etching, the inventors have successfully regulated the surface roughness of the doped polysilicon layer in the laser-opened region on the back side of the solar cell.

[0055] According to one embodiment of the present invention, step (2) and / or step (3) is performed in a hydrofluoric acid electrolyte;

[0056] Preferably, a cathode is added to the hydrofluoric acid electrolyte, and the cathode is preferably a titanium cathode;

[0057] More preferably, the surface of the titanium cathode is plated with platinum or rhodium-iridium alloy.

[0058] In a specific embodiment, the method of the present invention uses the same hydrofluoric acid electrolyte in the same electrolyte tank to successively complete the steps of removing the oxide layer in the laser opening area and roughening the surface of the doped polysilicon layer in the laser opening area. This method is easy to operate, low in cost, and does not damage the battery itself.

[0059] According to one embodiment of the present invention, in step (2), the hydrofluoric acid concentration of the hydrofluoric acid electrolyte is 1wt% to 3wt%, preferably 1.4wt% to 1.8wt%;

[0060] NH4F is used to adjust the pH value of the hydrofluoric acid electrolyte to 3-4, preferably 3.4-3.8.

[0061] When the hydrofluoric acid content in the electrolyte is lower than 1wt%, the electrochemical etching efficiency is slow; when the hydrofluoric acid content in the electrolyte is higher than 3wt%, the electrolyte will corrode the non-laser film-opening area of ​​the battery cell.

[0062] According to one embodiment of the present invention, in step (2), the temperature for cleaning and removing the oxide layer is 10° C. to 30° C., preferably 18° C. to 25° C.;

[0063] The time for cleaning and removing the oxide layer is 25S to 60S, preferably 30S to 50S.

[0064] During the laser film opening process of step (1), oxides are generated on the surface of the doped polycrystalline layer while removing the passivation layer. The oxides are removed using a hydrofluoric acid electrolyte, exposing the doped polycrystalline layer to facilitate subsequent electrochemical etching.

[0065] According to one embodiment of the present invention, in step (1), the width of the pattern formed in the laser film opening area is 35 μm to 60 μm, preferably 40 μm to 45 μm.

[0066] Since the pattern width formed by laser film opening is small, using a secondary laser method to open the film again will cause significant damage to the film opening area. The electrochemical etching method of the present invention overcomes this defect and can achieve an improvement in the grid line bonding strength without damaging the battery itself.

[0067] According to an embodiment of the present invention, the solar cell is a TOPCon cell or a HJT cell. Preferably, in step (4), the material of the back grid line is selected from one or more of the following: Ag, Cu, Ni, Sn.

[0068] After the electrochemical etching in step (3), the surface roughness of the doped polysilicon layer in the laser-opened area increases. At this time, electroplating of metal gate lines in this area can obtain better gate line bonding strength.

[0069] Example 1

[0070] This embodiment takes a TOPCon cell as an example to illustrate the method for preparing the back grid line of a solar cell of the present invention.

[0071] (1) A cell front structure including a metal grid line is prepared on the front side of the substrate of the TOPCon cell, and a tunneling oxide layer, a doped polysilicon layer and a passivation layer are sequentially prepared on the back side of the substrate of the TOPCon cell.

[0072] In a specific embodiment, the metal grid lines of the front structure of the TOPCon battery are arranged on the pyramid velvet structure on the substrate. Figure 3 A schematic diagram of the front grid structure of the battery is shown. Figure 3 As shown, the TOPCon battery front grid line structure 9 includes a plurality of battery front main grids 10, a plurality of battery front fine grids 11, and a plurality of PAD points 12 connecting the main grids and the fine grids.

[0073] (2) Laser film opening is used to remove the passivation layer at the grid line position on the back of the TOPCon battery.

[0074] The width of the pattern formed in the laser film opening area is 35 μm to 60 μm, preferably 40 μm to 45 μm.

[0075] In a specific embodiment, the width of the pattern formed in the laser film opening area is 42 μm.

[0076] (3) Clean and remove the oxide layer in the laser-opened area on the back of the battery.

[0077] During the laser film opening process in step (2), oxides are generated on the surface of the doped polycrystalline layer while the passivation layer is removed. The oxides are cleaned and removed to expose the doped polycrystalline layer.

[0078] Preferably, hydrofluoric acid is used to remove the oxide layer.

[0079] Wherein, the hydrofluoric acid concentration of the hydrofluoric acid electrolyte is 1wt% to 3wt%, preferably 1.4wt% to 1.8wt%.

[0080] NH4F is used to adjust the pH value of the hydrofluoric acid electrolyte to 3-4, preferably 3.4-3.8.

[0081] In a specific embodiment, the hydrofluoric acid concentration of the hydrofluoric acid electrolyte is 1.5 wt %, and NH 4 F is used to adjust the pH value of the hydrofluoric acid electrolyte to 3.6.

[0082] Wherein, the temperature for cleaning and removing the oxide layer is 10°C to 30°C, preferably 18°C ​​to 25°C;

[0083] The time for cleaning and removing the oxide layer is 25S to 60S, preferably 30S to 50S.

[0084] In a specific embodiment, the temperature for cleaning the oxide layer is 22° C., and the time for cleaning the oxide layer is 45 seconds.

[0085] (4) Using the laser-opened area on the back of the battery as the anode, electrochemically etching the doped polysilicon layer in the laser-opened area.

[0086] Figure 1 FIG. 1 is a schematic diagram showing electrochemical etching of the doped polysilicon layer in the laser-opened region. Figure 1 And its partial enlarged view Figure 2 As shown, after the step (3) of cleaning and removing the oxide layer, there is no need to replace the tank body and the electrolyte 6. Only a cathode 3 is added to the electrolyte tank body and the cathode 3 is connected to the negative electrode of the power source 1. At the same time, the positive electrode of the power source 1 is connected to the grid line 5 on the front side of the battery to form an anode 2. Since the passivation layer on the back of the TOPCon battery is not conductive, the electrolytic anode reaction occurs in the doped polysilicon layer in the laser film-opening area on the back of the TOPCon battery. After electrolytic etching, the roughness of the laser film-opening area is increased.

[0087] Figure 3 A schematic diagram showing the battery structure after electrochemical etching in Example 1 is shown. Figure 3 And its partial enlarged view Figure 4 As shown, observing the side surface 7 of the TOPCon battery, the laser-opened region 8 after electrochemical etching has increased roughness compared to the laser-opened region 4 before electrochemical etching.

[0088] In a preferred embodiment, both step (3) and step (4) are completed in a hydrofluoric acid electrolyte tank.

[0089] Wherein, the cell body also includes a cathode.

[0090] In a specific embodiment, a titanium electrode with a surface plated with platinum or rhodium-iridium alloy is used as the cathode plate.

[0091] By controlling the anodic oxidation current density, etching temperature and etching time of electrochemical etching, the surface roughness of the doped polysilicon layer in the laser-opened area on the back of the TOPCon cell is regulated.

[0092] Among them, the anodic oxidation current density in electrochemical etching is 0.5A / dm 2 ~2A / dm 2 , preferably 1A / dm 2 ~1.5A / dm 2 ;

[0093] The temperature of electrochemical etching is 10°C to 30°C, preferably 18°C ​​to 25°C;

[0094] The electrochemical etching time is 30S to 85S, preferably 40S to 60S.

[0095] In one embodiment, the electrochemical etching anodization current density is 1.2 dm 2 , the electrochemical etching temperature is 22°C, and the electrochemical etching time is 45S. Figure 6 and Figure 7 The transmission electron microscope images of the laser-opened area before and after electrochemical etching are shown respectively. It can be seen from the images that after electrochemical etching, the roughness of the laser-opened area (gate line area) is significantly improved, which is beneficial to increase the gate line bonding force and improve the gate line pull-off force.

[0096] (5) After the electrochemical etching of step (4) is completed, the back metal grid line is electroplated in the roughened laser-opened area.

[0097] In a specific embodiment, Ni-Cu-Ag gate lines are electroplated in the laser-opened area, and the electroplating conditions are: nickel plating current 400mA, electroplating time 2.5min, copper plating current 1600mA, electroplating time 4min, chemical silver plating 1min.

[0098] By roughening the laser-opened area, the bonding strength of the back grid lines is enhanced without increasing the electroplating process time and without the need for additional electroplating equipment and processes.

[0099] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.

Claims

1. A method for preparing a back grid line of a solar cell, characterized in that: The method comprises the following steps: (1) performing laser film opening on the back side of the solar cell in the area where the back side grid lines are to be formed; (2) Cleaning and removing the oxide layer in the laser-opened area on the back of the solar cell; (3) using the laser-opened film area on the back of the solar cell as an anode, electrochemically etching the laser-opened film area to increase the roughness of the laser-opened film area; (4) Making backside grid lines in the laser film opening area; Wherein, step (2) and step (3) are completed in a hydrofluoric acid electrolyte, and the hydrofluoric acid concentration of the hydrofluoric acid electrolyte is 1wt% to 3wt%.

2. The method according to claim 1, characterized in that In step (3), the positive electrode of the power source is connected to the metal grid line of the front structure of the solar cell to form the anode.

3. The method according to claim 1 or 2, characterized in that: In step (3), the anodic oxidation current density in the electrochemical etching is 0.5A / dm 2 ~2A / dm 2 ; The temperature of the electrochemical etching is 10°C to 30°C; The electrochemical etching time is 30S to 85S.

4. The method according to claim 3, characterized in that In step (3), the anodic oxidation current density in the electrochemical etching is 1A / dm 2 ~1.5A / dm 2 ; The temperature of the electrochemical etching is 18°C ​​to 25°C; The electrochemical etching time is 40S to 60S.

5. The method according to claim 1, characterized in that Add a cathode to the hydrofluoric acid electrolyte.

6. The method according to claim 5, characterized in that The cathode is a titanium cathode.

7. The method according to claim 6, characterized in that The surface of the titanium cathode is plated with platinum or rhodium-iridium alloy.

8. The method according to claim 1, characterized in that: The hydrofluoric acid concentration of the hydrofluoric acid electrolyte is 1.4wt% to 1.8wt%; and / or NH4F is used to adjust the pH value of the hydrofluoric acid electrolyte to 3 to 4.

9. The method according to claim 8, characterized in that NH4F is used to adjust the pH value of the hydrofluoric acid electrolyte to 3.4-3.

8.

10. The method according to claim 1, characterized in that In step (2), the temperature for cleaning and removing the oxide layer is 10° C. to 30° C.; and the time for cleaning and removing the oxide layer is 25S to 60S.

11. The method according to claim 10, characterized in that In step (2), the temperature for cleaning and removing the oxide layer is 18° C. to 25° C.; and the time for cleaning and removing the oxide layer is 30S to 50S.

12. The method according to claim 1, characterized in that In step (1), the width of the pattern formed in the laser film opening area is 35 μm to 60 μm.

13. The method according to claim 12, characterized in that In step (1), the width of the pattern formed in the laser film opening area is 40 μm to 45 μm.

14. The method according to claim 1, characterized in that The solar cell is a TOPCon cell or a HJT cell.

15. The method according to claim 1, characterized in that In step (4), the material of the back gate line is selected from one or more of the following: Ag, Cu, Ni, Sn.

Citation Information

Patent Citations

  • Solar cell and preparation method thereof

    CN116565036A

  • Solar cell and mfg. method thereof

    CN1369919A